Perception of Indian Dental Students to Pursue Higher Education Abroad during COVID-19 - Niharika Singh; Sonia Gupta; Kalyana Chakravarthy Pentapati; Abhinav Tadikonda (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate Indian dental students' perception of seeking international dental higher education during COVID-19. Material and Methods: We conducted an online survey among the dental students. A self-administered questionnaire was prepared, which had information on country choice, reasons for the decision to study abroad, measures to be taken by the foreign universities because of COVID-19, the application's status, current plan, and opinions on exploring other possibilities. Results: Four hundred students constituted the final sample, out of which the majority were females (69.3%). Most of the students were not sure about their status in the application process (63%). The current plan to study abroad remained uncertain for almost half of the students (50.2%). Concerning the status of the application process, a significantly higher number of female students were "not sure" and are still "searching colleges" (p<0.001). Similarly, a higher number of females were "uncertain" or "postponed" or "canceled" when compared to the males concerning the current plan to study abroad (p=0.001). Also, a significantly higher proportion of female students cited the study budget as the main deterrent for pursuing a career abroad and opined that "flexible study options" will help them get admissions post-COVID-19 (p=0.001 and 0.035). Conclusion: A substantial impact was perceived by Indian dental students concerning higher education abroad, more among females.